THU0239 Association of the 2/2 Genotype of the Enhancer Hs1, 2A of the IG Heavy 3' Regulatory Region with Early Rheumatoid Arthritis. (10th June 2014) - Tolusso, B.; Gremese, E.; Fedele, A.L.; Frezza, D.; Canestri, S.; Cianci, F.; Gigante, M.R.; Di Mario, C.; Ferraccioli, G.
Abstract : Background: The allele*2 of the enhancer HS1, 2A (IgH 3'RR-1) has been shown to have a binding site for NK-kB and to be associated to Rheumatoid Arthritis (RA), Systemic Lupus Erythematosus and Systemic Sclerosis. Objectives: To study a polymorphism in the enhancer HS1, 2A as a biomarker of disease activity and response to therapy in early RA. Methods: 320 early RA (ERA) (age: 54.4±14.1 years; 76.3% female; 62.8% anti-CCP positive) were enrolled in the study. ERA patients fulfilled the 2010 American College of Rheumatology classification criteria for RA and were treated according to a tight control strategy. At baseline and every 3 months demographic and immunological data and the ACR/EULAR core data set were recorded. At each visit, clinical improvement and remission were evaluated according to DAS [1, 2]. Patients were genotyped for HS1, 2A enhancer polymorphism, as previously described [3]. Baseline IL-6 and BAFF plasma levels were evaluated by ELISA's methods. Results: The analysis of the genotype's distribution of the HS1, 2A enhancer showed a higher frequency of the 2/2 genotype in ERA patients (28.1%) compared to healthy subjects (14.9%, p<0.001 ). At diagnosis, ERA patients carrying the 2/2 genotype had a higher baseline inflammatory status (ESR: 49.6±30.5 mm/1st hr, CRP: 30.6±40.5 mg/l, IL6: 27.3±45.8 pg/ml) and higher disease activity (DAS28: 5.6±1.3, SDAI: 33.3±15.6) and disability (HAQ:1.3±0.8) compared to patients without the 22 genotype (ESR: 37.6±25.7 mm/1st hr, p=0.002; CRP: 20.1±27.3 mg/l, p=0.04; IL6: 20.6±38.5 pg/ml, p=0.04; DAS28: 5.3±1.3, p=0.05; SDAI: 29.2±14.1, p=0.06; HAQ:1.1±0.7, p=0.03). Similar autoantibody patterns were seen in the different genotypes. Fifty-three percent of ERA patients reached a good-EULAR response at 3 months follow-up visit (FU) and 24% were in sustained EULAR-remission at 6 months FU. The percentage of good-EULAR response at 3-months FU and sustained EULAR-remission at 6-month FU was lower in ERA patients carrying the 2/2 genotype compared with ERA patients without the 2/2 genotype [good-EULAR response: 36.2% vs 58.8%, OR (95%CIs): 0.40 (0.21-0.74); sustained EULAR-remission: 10.9% vs 27.9%, OR: 0.32 (0.13-0.79)]. Moreover, ERA patients carrying the 2/2 genotype were characterized by a higher percentage of subjects treated with TNF-blockers at 6 months FU compared with patients without the 2/2 genotype (20.3% vs 8.8%, p=0.02 ). Circulating B cells of subjects carrying the allele*2 showed a higher expression (fold change) of BAFF-R (7.6±3.7) and IL6 (4.1±6.4) than carriers of the 1/1 genotype (BAFF-R: 3.3±1.5, p=0.05; IL-6: 0.9±0.8, p=0.07). Conclusions: The presence of the 2/2 genotype of the enhancer HS1, 2A seems to identify a more active and aggressive disease in ERA patients poorly responsive to DMARDs. The presence of a binding site for NF-kB in the allele*2 (4), could explain the more aggressive phenotype. References: van Gestel AM., Arthritis and Rheumatism, 1996. Prevoo ML, British Journal of Rheumatology, 1996. Tolusso B et al., Ann Rheum Dis 2009. Frezza D et al., Ann Rheum Dis 2012. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.3591